KONTRUKSI BUDAYA NGOPI BAGI GENERASI MILLENIAL DI KOTA KEDIRI - Irawan, Darwin; Fauji, Diah Ayu Septi; Sari, Lita Deviana; Al-Aradatin, Sulton Ali (Universitas Nusantara PGRI Kediri, 2020)
Coffee is transformed into a contemporary culture that is closely related to lifestyle trends. This change in meaning is closely related to the construction that is formed by the community or due to modernization and globalization that is increasingly fast. So what meaning does the coffee construction built by the current millennial generation? Why is it different from past constructions? Based on these questions, it is interesting for the author to conduct research in an effort to identify the meaning of the millennial generation of the current coffee habits and construct the coffee culture of the millennial generation in Kediri. By using an ethnometodological approach, the authors get a building picture of the meaning of coffee for millennials in Kediri. Which results include: Convenience, Social Bounding, Self-actualization & Community Existence. Research can provide scientific benefits related to how the meaning of coffee culture will certainly describe the reality conditions of an area in general. Thus, the results of research findings can be used by various parties, both the government in determining policies and for entrepreneurs in determining competitive strategies for business.